Colles external fixator as alternative in comminuted mandibular fractures treatment (Research, Society and Development, 2020)
Objective: to report a surgical case of comminuted mandible fracture caused by a firearm projectile treated with external fixation. Methodology: male patient, 18 years old, attended the Emergency Department of the Maxillofacial Surgery service after trauma in the mandibular region by a firearm projectile. On clinical examination, edema was observed in the cervical zone II and mandibular region, penetrating orifice of entry of the projectile in the genial region and mobility in the mandibular body. CT scan revealed a comminuted fracture in the mandible. Transcutaneous perforations were performed with pins, anatomical reduction of the fracture and stabilization to the external nail, adapting to the mandibular anatomy. Following postoperative follow-up, the patient progresses without pain complaints, with functional and satisfactory mouth opening, without mobility in bone fragments, and reestablished mandibular framework. Results and Conclusion: mandibular fractures by firearms are frequent in the routine of the buccomaxillofacial surgeon. Cases of bone comminution present individual peculiarities that must be taken into account in their management. The correct indication of external fixation proved to be adequate and satisfactory for cases of mandible comminution.